Potency of Chitosan and Chitooligochitosan (COS) as Prebiotics for Streptococcus thermophillus and Lactobacillus bulgaricus Probiotics - Ervia Yudiati; Sri Sedjati; Adha Susanto; Nuril Azhar; Rabia Alghazeer (Jurnal Kelautan Tropis, 2021)
Lately, chitosan as a result of chitin deacetilation has known as potencial compound as food industry, pharmacy and environmental agents. The weakness of chitosan is the low water solubility and high viscosity. The size reduction by cutting the β-1, 4 glicosidic bond to improve the bioactivity is the alternative solution. This research aims to find out the addition of chitosan and COS for the Streptococcus thermophillus FNCC – 0041 and Lactobacillus bulgaricus FNCC – 0040 probiotics bacteria culture. S. thermophillus and L. bulgaricus were cultured in the MRS Broth media with addition of Commercial Chitosan (CC), Commercial Oligochitosan (COC), Self-production Chitosan (PC) and Self-production Oligochitosan (POC) in different doses (0.05; 0.1; and 0.2 mg.ml-1). Percentage DD on those treatments was similar. The spectra vibration of  The FT-IR analysis of PC and POC were fit to the CC and COC. In chitosan treatments, the best growth of S. thermophilus was reached at 0.2 mg/mL PC, while in chitooligochitosan was from 0.20 mg/mL COC treatments, respectively. The addition of different type of chitosan have a significant effect (p<0.05) to the growth of S. thermophillus, but have not resulted the significant effect to the L. bulgaricus (p>0.05) growth. So, therefore the addition of chitosan and COS as prebiotics for the probiotics were in dose dependant manner. Compare to chitosan commercial, our chitosan production have a good potency to be developed.